Presepsi Peserta Diklat Penilaian Pembelajaran terhadap Pemanfaatan Aplikasi Class123 untuk Penilaian Sikap - Ratna Prilianti (Balai Diklat Keagamaan Semarang, 2020)
The purpose of this study was to measure the training participants' perceptions of the usefulness and ease of use of Class123 for attitude assessment. This research is a descriptive research with survey method. This research was conducted at the Semarang Religious Education and Training Center, especially in the Learning Assessment Functional Technical Training. The number of training participants was 35 teachers who described their perceptions about the use of the Class123 application to assess attitudes. The results showed the training participants' perceptions of the ease of use of Class123 where in the range of 51.43% - 62.86% of the respondents stated strongly agree on the questionnaire items 1 and 3. The training participants' perception of the benefits of the Class123 Application shows the results of the respondents stated strongly agree as much as 60% -91.43% of respondents in the item questionnaire of the 4th statement and the 1st statement. Keywords: perception, Class123, attitude assessment